PERAN PENYULUHAN DALAM KEGIATAN PENCEGAHAN DAN PENGENDALIAN PENYAKIT MULUT DAN KUKU (PMK) BESERTA KENDALANYA DI KABUPATEN MOJOKERTO (The Role of Counseling in the Prevention and Control of Foot and Mouth Disease (FMD) and its Constraints in Mojokerto Regency) - CAHYANI, TRINI NUR; MAYASARI, DITA APRILIA; WULANDARI, DWI RAHAYU SRI (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2023)
Foot and Mouth Disease (FMD) in livestocks has become an epidemic in Mojokerto Regency which has caused significant economic losses, so it is necessary to carry out prevention and control. FMD prevention and control activities at the village and sub-district levels are facilitated by agricultural extension workers through Communication, Information and Education (CIE) counseling activities for breeders. This study aims to determine the role of counseling in prevention and control of FMD and the obstacles it faces. The data collection is based on online questionnaires which were distributed in 63 agriculture extension civil servants in 18 sub-districts in Mojokerto Regency. The research shows that majority of the officers have implemented CIE in all of their target areas. The counseling methods based on information technique used was direct counseling and a combination of direct and indirect counseling. The majority of counseling used printed media that contain specific materials of treatments. This study also measured the acceptance and support of stakeholders at the village level. Obstacles encountered in the field included coordination constraints, terrain and location of stables, negative issues that developed in the community and aggressive cattle conditions.